Energy barriers for collapsing large-diameter carbon nanotubes. (15th April 2020) - Del Grande, R.R.; Fonseca, Alexandre F.; Capaz, Rodrigo B.
Abstract: Single-wall carbon nanotubes (SWNTs) are best known in their hollow cylindrical shapes, but the ground state of large-diameter tubes actually corresponds to a collapsed dumbbell-like structure, where the opposite sides of the nanotube wall are brought in contact and stabilized by van der Waals attraction. For those tubes, the cylindrical shape is metastable and it is interesting to investigate the energy barrier for jumping from one configuration to another. We calculate the energy barrier for SWNT collapse by considering a transition pathway that consists of an initial local deformation that subsequently propagates itself along the SWNT axis. This leads to finite and physically meaningful energy barriers in the limit of infinite nanotubes. Yet, such barriers are surprisingly large (tens of eV) and therefore virtually unsurmountable, which essentially prevents the thermal collapse of a metastable cylindrical at any reasonable temperatures. Moreover, we show that collapse barriers increase counterintuitively with SWNT diameter. Finally, we demonstrate that, despite such huge barriers, SWNTs may collapse relatively easily under external radial forces and we shed light on recent experimental observations of collapsed and cylindrical SWNTs of various diameters. Graphical abstract: Image 1